Distribution of high-risk human papillomavirus genotypes in precancerous cervical lesions in ouagadougou, Burkina Faso. Issue 1 (2016) - Ouédraogo, Charlemagne; Zohoncon, Théodora Mahoukèdè; Traoré, Esther M. A.; Ouattara, Souleymane; Bado, Prosper; Ouedraogo, Clarisse T.; Djigma, Florencia W.; Ouermi, Djénéba; Obiri-Yeboah, Dorcas; Lompo, Olga; Akpona, Simon A.; Simpore, Jacques
No abstract available